Penal humanitarianism beyond the nation state: An analysis of international criminal justice - Lohne, Kjersti (Theoretical criminology, 2020)
In a recent account of border control, Mary Bosworth introduces the notion of ‘penal humanitarianism’ to describe how humanitarianism enables penal power to move beyond the nation state. Based on a study of international criminal justice, this article applies and develops the notion of penal humanitarianism, and argues that that power to punish is particularly driven by humanitarian reason when punishment is disembedded from the nation state altogether. Disguising the fact of situatedness through claims to the global and universal, international criminal justice is not only a product of situated relations of power, but also constitutes new geographies of penal power. By complicating notions of humanitarianism, penal power and the state, international criminal justice raises interesting questions about the epistemological privilege of the nation state framework in the sociology of punishment.